The big book of dashboards : visualizing your data using real-world business scenarios - Wexler, Steve, 1958-; Shaffer, Jeffrey, 1972-; Cotgreave, Andy, 1972- (Hoboken, New Jersey : John Wiley & Sons, Inc., 2017)
"The definitive reference book with real-world solutions you won't find anywhere else The Big Book of Dashboards presents a comprehensive reference for those tasked with building or overseeing the development of business dashboards. Comprising dozens of examples that address different industries and departments (healthcare, transportation, finance, human resources, marketing, customer service, sports, etc.) and different platforms (print, desktop, tablet, smartphone, and conference room display) The Big Book of Dashboards is the only book that matches great dashboards with real-world business scenarios. By organizing the book based on these scenarios and offering practical and effective visualization examples, The Big Book of Dashboards will be the trusted resource that you open when you need to build an effective business dashboard. In addition to the scenarios there's an entire section of the book that is devoted to addressing many practical and psychological factors you will encounter in your work. It's great to have theory and evidenced-based research at your disposal, but what will you do when somebody asks you to make your dashboard 'cooler' by adding packed bubbles and donut charts? The expert authors have a combined 30-plus years of hands-on experience helping people in hundreds of organizations build effective visualizations. They have fought many 'best practices' battles and having endured bring an uncommon empathy to help you, the reader of this book, survive and thrive in the data visualization world. A well-designed dashboard can point out risks, opportunities, and more; but common challenges and misconceptions can make your dashboard useless at best, and misleading at worst. The Big Book of Dashboards gives you the tools, guidance, and models you need to produce great dashboards that inform, enlighten, and engage"--
"In The Dashboard Book, the authors will lay out a variety of examples of successful dashboards so that the reader can find a scenario that closely matches what he or she is tasked with visualizing"--
Part I.A Strong Foundation. Chapter 1. Data Visualization: A Primer -- Part II. The Scenarios. Chapter 2. Course Metrics Dashboard ; Chapter 3. Comparing Individual Performance with Peers ; Chapter 4. What-If Analysis: Wage Increase Ramifications ; Chapter 5. Executive Sales Dashboard ; Chapter 6. Ranking by Now, Comparing with Then ; Chapter 7. Are We On Pace to Reach Our Goals? ; Chapter 8. Multiple Key Performance Metrics ; Chapter 9. Power Plant Operations Monitoring ; Chapter 10. Showing Year-to-Date and Year-over-Year at the Same Time ; Chapter 11. Premier League Player Performance Metrics ; Chapter 12. RBS 6 Nations Championship Match Performance Analysis ; Chapter 13. Web Analytics ; Chapter 14. Patient History Analysis of Recent Hospital Admissions ; Chapter 15. Hospitality Dashboard for Hotel Management ; Chapter 16. Sentiment Analysis: Showing Overall Distribution ; Chapter 17. Showing Sentiment with Net Promoter Score ; Chapter 18. Server Process Monitoring ; Chapter 19. Big Mac Index ; Chapter 20. Complaints Dashboard ; Chapter 21. Hospital Operating Room Utilization ; Chapter 22. Showing Rank and Magnitude ; Chapter 23. Measuring Claims across Multiple Measures and Dimensions ; Chapter 24. Showing Churn or Turnover ; Chapter 25. Showing Actual versus Potential Utilization ; Chapter 26. Health Care Provider Productivity Monitoring ; Chapter 27. Telecom Operator Executives Dashboard ; Chapter 28. The Economy at a Glance ; Chapter 29. Call Center -- Part II. Dashboards in the Real World. Chapter 30. Want to Engage People? Make Your Dashboards Personal ; Chapter 31. Visualizing Time ; Chapter 32. Beware the Dead-End Dashboard ; Chapter 33. The Allure of Red and Green ; Chapter 34. The Allure of Pies and Donuts ; Chapter 35. Clouds and Bubbles ; Chapter 36. A journey into the unknown.
Machine generated contents note: Introduction Part I A Strong Foundation Chapter 1 Data Visualization: A Primer Part II The Scenarios Chapter 2 Course Metrics Dashboard Chapter 3 Comparing Individual Performance with Peers Chapter 4 What-If Analysis: Wage Increase Ramifications Chapter 5 Executive Sales Dashboard Chapter 6 Ranking by Now, Comparing with Then Chapter 7 Are We On Pace to Reach Our Goals? Chapter 8 Multiple Key Performance Metrics Chapter 9 Power Plant Operations Monitoring Chapter 10 Showing Year-to-Date and Year-over-Year at the Same Time (YTD and YOY) Chapter 11 Premier League Player Performance Metrics Chapter 12 RBS 6 Nations Championship Match Performance Analysis Chapter 13 Web Analytics Chapter 14 Patient History Analysis of Recent Hospital Admissions Chapter 15 Hospitality Dashboard for Hotel Management Chapter 16 Sentiment Analysis: Showing Overall Distribution Chapter 17 Showing Sentiment with Net Promoter Score Chapter 18 Server Process Monitoring Chapter 19 Big Mac Index Chapter 20 Complaints Dashboard Chapter 21 Hospital Operating Room Utilization Chapter 22 Showing Rank and Magnitude Chapter 23 Measuring Claims across Multiple Measures and Dimensions Chapter 24 Showing Churn or Turnover Chapter 25 Showing Actual versus Potential Utilization Chapter 26 Health Care Provider Productivity Monitoring Chapter 27 Telecom Operator Executives Dashboard Chapter 28 The Economy at a Glance Chapter 29 Call Center Part III Dashboards in the Real World Chapter 30 Want to Engage People? Make Your Dashboards Personal Chapter 31 Visualizing Time Chapter 32 Beware the Dead-End Dashboard Chapter 33 The Allure of Red and Green Chapter 34 The Allure of Pies and Donuts Chapter 35 Clouds and Bubbles Chapter 36 A journey into the unknown Index.
Includes bibliographical references and index.
Keywords: Dashboards (Management information systems); Organizational effectiveness -- Evaluation; Management -- Evaluation; Information technology; Data communications; Computer graphics; Business intelligence; Communication of information